Strategi Manajemen untuk Keunggulan Kompetitif di Bidang Pendidikan - Hesti Kusumaningrum; Syabillah Azzahra; Syakirah Rahma Putri; Siti Aisyah (Student Scientific Creativity Journal, 2023)
Strategic management is an analysis, decisions and actions taken by an organization to create and maintain a competitive advantage. This research method uses literature review research conducted by collecting and analyzing related literature from international and national sources in the form of books, journals, and articles. Based on this research, the application of strategic management science in educational institutions can face various challenges due to continuous change and competition and produce educational products (outputs) that are able to display high performance. The purpose of this research is to conduct an analysis related to the understanding and implementation of strategic management in creating a competitive advantage in the field of education, this research also aims to provide an in-depth understanding of the concept of strategic management and how its application can help educational institutions face the challenges of globalization and improve the quality of education. This research also highlights the urgency of implementing strategic management in educational institutions, given the challenges faced due to globalization and increasingly fierce competition. Strategic management is considered the key to creating a competitive advantage for educational institutions, enabling them to control their schools effectively and efficiently and produce superior quality graduates.